(untitled) (Riset Sains dan Teknologi Kelautan, 2026)
Reliable electricity supply for the archipelagic regions of Eastern Indonesia motivates the assessment of floating nuclear power plants (FNPPs) as low-carbon baseload sources. This study revises and expands a conceptual motion-response assessment of a 250 MWe spar-type FNPP proposed for Halmahera waters. The model base consists of a 45 m diameter cylindrical structure, a total height of 73 m, a draft of 48.5 m, a modeled water depth of 150 m, and a nine-line spread-mooring system. Hydrodynamic behavior is evaluated in the frequency domain using a six-degree-of-freedom framework and the ANSYS-AQWA outputs available from the original study. Regular-wave responses are interpreted through response amplitude operators (RAOs), while irregular-wave behavior is assessed through response spectra and stochastic amplitudes. Directional patterns are physically consistent: maximum surge is 1.825 m at 0° wave heading, maximum sway is 1.825 m at 90°, heave is 0.226 m for all headings, maximum roll is 0.532° at 90°, and maximum pitch is 0.532° at 0°. All responses remain below the adopted screening criteria of 12 m for surge/sway, 1.3 m for heave, and 45° for roll/pitch. Nevertheless, satisfying these thresholds demonstrates only preliminary hydrodynamic feasibility and does not constitute a nuclear safety case. Site-specific metocean validation, mooring-line tension and one-line-damaged analyses, nonlinear time-domain simulations, tsunami assessment, and qualification of safety-related equipment are required before advancing the concept to a technical pre-feasibility stage.